Evaluation of the performance of eco-friendly lightweight interlocking concrete paving units incorporating sawdust wastes and laterite. Issue 1 (31st December 2016) - Sojobi, Adebayo Olatunbosun
Abstract: This research investigates the performance of sawdust wastes and laterite as an alternative lightweight fine aggregate and cementitious material respectively in eco-friendly lightweight interlocking concrete paving units (ICPU) using a mix ratio of 1:2:4. The lightweight sawdust and laterite were studied due to their abundant availability as industrial waste and cheap local construction material. Eco-friendly ICPU is a low-strength concrete with compressive strengths of 6.02–7.57 and 3.66–4.52 N/mm 2 at 5 and 10% sawdust replacements with bulk density ranges of 1, 756.62–1, 810.9 and 1, 522.89–1, 532.4 kg/m 3 respectively which exceeded the minimum compressive strength requirement of 3.45 N/mm 2 in non-load bearing concrete applications. Though air curing recorded higher compressive strengths at early curing ages, water curing was recommended to facilitate complete hydration owing to the hygroscopic nature of the sawdust. The packing and filling effects of the lightweight sawdust coupled with the combined pozzolanic properties of the sawdust waste and laterite seemed to have contributed to the slight increase in CS of the eco-friendly ICPU when heated. Effective partnerships among the State and Local Government Waste Management Authorities, sawmill operators and informal waste collectors were recommended for effective sawdust waste recovery, storage and usage in eco-friendly construction.